Women’s Empowerment and Poverty Reduction: Panel Evidence on Labor and Education Dynamics - Aiman Farooq; Dr. Maria Sultana; Dr. Rehana Naheed; Qadeer Khan (Indus Journal of Social Sciences, 2025)
In a world where gender dynamics shape economic realities, this study delves into the transformative role of female labor force participation (FLFP) and education in combating poverty. Analyzing panel data from 30 countries spanning 2012 to 2023, it examines the interplay between FLFP, the primary completion rate of females (PCRF), and poverty headcount ration (PHR). The findings reveal that higher FLFP directly boosts household incomes, fostering economic stability, while enhanced PCRF empowers women to access better job opportunities, amplifying poverty reduction. Utilizing advanced econometric techniques, including GMM and quantile regression, this study highlights the untapped potential of women’s participation in the workforce and the pivotal role of education in poverty alleviation. Policymakers are urged to prioritize strategies that integrate gender equality in education and employment, ensuring equitable economic growth and a brighter future for all. By weaving together FLFP, education and poverty into a cohesive narrative, this study offers a profound understanding of the mechanisms driving poverty alleviation. It serves as a clarion call for action, emphasizing that empowering women is not just a moral imperative but an economic necessity for sustainable development.